The relationship of sociodemographic and clinical profiles to the duration of untreated psychosis among adolescents with first-episode psychosis in an Oman tertiary hospital. Issue 2 (2nd April 2020) - Mirza, Hassan; Al-Huseini, Salim; Al-Shamli, Siham; Al-Dhahri, Maissa; Al-Rashdi, Zainab; Al-Hosni, Amira; Al-Hasani, Haya; Jaju, Sanjay; Al-Sibani, Nasser; Al-Adawi, Samir
ABSTRACT: Background : The duration of untreated psychosis (DUP) among adolescents with first-episode psychosis has received scant attention in non-western societies. Aim : This study aims to explore both sociodemographic and clinical profiles and examine their relationship to the DUP among adolescents with first-episode psychosis admitted to a tertiary care hospital in Oman Method : This is a retrospective, cross-sectional, analytical study conducted at a tertiary care hospital in Oman from January 2010 to December 2018. The subjects of the study included 121 drug-naive adolescents between the ages of 10 and 19 years old with first-episode psychosis. Sociodemographic data and risk factors were also solicited. Result : A total of 121 adolescents fulfilled the study criteria. The mean DUP was 4 months (SD 4.5). Place of residence, family history of psychosis, presence of both positive and negative symptoms, use of traditional healing systems, length of stay, and leaving against medical advice were the significant factors associated with the duration of untreated psychosis. Discussion : Some of the factors presently found to contribute to the DUP could lay the groundwork for the reduction in the duration of untreated psychosis and redesigning services for such population.